The fertility transition in Sub-Saharan Africa: The role of structural change - Nicolas Büttner; Michael Grimm; Isabel Günther; Kenneth Harttgen; Stephan Klasen (Universität Passau, Wirtschaftswissenschaftliche Fakultät, 2022)
Despite relatively sustained economic growth in at least parts of Sub-Saharan Africa over the past twenty years, the fertility transition has not much advanced in most countries in that region. We explore whether the lack of structural change can explain this slow transition. For this end, we analyze the determinants of fertility transitions across the developing world using a novel regional level panel dataset created by matching Demographic and Health Surveys and Household Income Surveys from 60 countries over three decades. Our key hypothesis is that structural change, i.e. a shift of employment from subsistence agriculture to more skill-intensive services, accompanied by an increase in human capital accumulation, is a key driver of the fertility transition. Our results indicate that higher education of women, female employment in non-agricultural formal jobs and industrialization as measured by an increase in nighttime light intensity are indeed important determinants of the fertility transition. We also find suggestive evidence for a complementary role of access to health insurance. Simulations show that if high-fertility countries in Sub-Saharan Africa had experienced the same structural change as the most demographically advanced regions in our sample over the last twenty years, fertility levels would be up to 40% lower.
Keywords: D13; J11; J13; J22; O12; 330; Demographic transition; Fertility; Structural change; Human capital; Sub-SaharanAfrica